PENGARUH FAKTOR RESPON KONSUMEN TERHADAP CITRA BISNIS JASA KARAOKE KELUARGA INUL VIZTA (Studi Evaluasi Pemasaran PT. Vizta Pratama Pekanbaru) - Indah Septiani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
As for the problem in this research was the shortage of the consumer's response that it was demonstrated with the sale target of the room had been reached and tended to descend each year. Moreover the existence of the perception from the community uptil now against the place of entertainment karaoke was to be the place that was not good, because uptil now entertainment karaoke was the immoral place and the other criminal action, like illegal drugs, alcohol, etc.. The aim of this research was to know the consumer's response and the business image from the service business karaoke the family of Inul Vizta as well as knew the influence of the consumer's response to the image of the service business karaoke the family of Inul Vizta. This research analysed the data by using the descriptive method and to reply the hypothesis that was put forward was carried out by the analysis of statistics used linear regression simple. Results of the research concluded that the consumer's response has it was thought been good and the image of the service business karaoke the family of Inul Vizta on the whole it was thought has been good. Was based on results of the analysis of the data through the analysis of statistics could be learnt that the consumer's response had relations that was towards the business image. The consumer's response gave the influence that was positive and significant towards the business image, so as if the consumer's response increased then will cause the increase towards the business image.Key Words: Response Of Consumers, Business, Marketing Image.